UNDERSTANDING OF CULINARY MICRO, SMALL AND MEDIUM ENTERPRISES ACTORS ON HALAL FOOD PRODUCTS IN SAMBAS REGENCY - Miswinda; Zarul Arifin; Wulan Purnamasari (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2023)
This research is motivated by a lack of understanding of halal products and foods, therefore researchers feel interested in researching the challenge of understanding the halalness of food so that culinary micro, small and medium enterprises actors are not careless in serving food to consumers. This study aims to obtain clear information about: 1) Knowing the understanding of culinary micro, small and medium enterprises actors on halal food products in Sambas Regency, 2) Knowing the application of culinary micro, small and medium enterprises actors to halal food products in Sambas Regency, 3) Knowing the benefits of understanding halal food products for culinary micro, small and medium enterprises actors in Sambas County. The subjects in the study were culinary micro, small and medium enterprises actors who had attended halal supervisor training in Sambas district. To obtain data related to the focus of the study, researchers conduct interviews, observations and documentation. The data validity check techniques used are: 1) Triangulation Technique, 2) Member Check Technique. The results of the study can be concluded: 1) Understanding of culinary micro, small and medium enterprises actors on halal food products in Sambas Regency, namely the understanding that micro, small and medium enterprises actors have met halal standards in Islam by referring to Halal Product Assurance Organizing Agency and the Indonesian Ulema Council and evidenced by the issuance of halal certificates on existing culinary micro, small and medium enterprises products Kabulaten Sambas. 2) The application of culinary micro, small and medium enterprises actors (businesses, micro and medium) to halal food products in Sambas Regency is carried out by paying attention to cleanliness in food, paying attention to packaging and how to serve food, always preparing hand washing before entering the food place. 3) The benefits for culinary micro, small and medium enterprises actors (businesses, micro and medium) in halal food products in Sambas Regency are that the body becomes healthy both physically and spiritually, the food that will eat is always maintained for comfort, security, and safety in consuming goods and/or services.